Formulation development of a live attenuated human rotavirus (RV3-BB) vaccine candidate for use in low- and middle-income countries. Issue 7 (3rd July 2021) - Kumar, Prashant; Shukla, Ravi S.; Patel, Ashaben; Pullagurla, Swathi R.; Bird, Christopher; Ogun, Oluwadara; Kumru, Ozan S.; Hamidi, Ahd; Hoeksema, Femke; Yallop, Christopher; Bines, Julie E.; Joshi, Sangeeta B.; et al.
ABSTRACT: Formulation development was performed with the live, attenuated, human neonatal rotavirus vaccine candidate (RV3-BB) with three main objectives to facilitate use in low- and middle- income countries including (1) a liquid, 2–8°C stable vaccine, (2) no necessity for pre-neutralization of gastric acid prior to oral administration of a small-volume dose, and (3) a low-cost vaccine dosage form. Implementation of a high-throughput RT-qPCR viral infectivity assay for RV3-BB, which correlated well with traditional FFA assays in terms of monitoring RV3-BB stability profiles, enabled more rapid and comprehensive formulation development studies. A wide variety of different classes and types of pharmaceutical excipients were screened for their ability to stabilize RV3-BB during exposure to elevated temperatures, freeze-thaw and agitation stresses. Sucrose (50–60% w/v), PEG-3350, and a solution pH of 7.8 were selected as promising stabilizers. Using a combination of an in vitro gastric digestion model (to mimic oral delivery conditions) and accelerated storage stability studies, several buffering agents (e.g., succinate, adipate and acetate at 200 to 400 mM) were shown to protect RV3-BB under acidic conditions, and at the same time, minimize virus destabilization during storage. Several optimized RV3-BB candidate formulations were identified based on negligible viral infectivity losses during storage at 2–8°C and −20°C for up to 12 months, as well as by relative stability comparisons at 15°C and 25°C (up to 12 and 3 months, respectively). These RV3-BB stability results are discussed in the context of stability profiles of other rotavirus serotypes as well as future RV3-BB formulation development activities.